O efeito antinociceptivo da corrente interferencial não é mediado por receptores opioides mu e delta espinhais e supraespinhais em ratos artríticos - Cruz, Kamilla Mayara Lucas da (2014)
Interferential Current therapy (IFC) has been widely used to manage different pain conditions in clinical practice. However, to this date, no studies have investigated the neurobiological mechanisms of action of this analgesic current. This study aimed to investigate the effects of IFC on hypernociception caused after joint inflammation induction and whether the opioid system is involved in the nociception produced at the rostral ventral medulla (RVM) and spinal cord. Were utilized 63 wistar rats, split into three experimental series: Behavioral serie: Interferential current; Morphine; Control. Spinal blockade serie: IFC+Naltrindole; IFC+Naloxone; IFC+Vehicle; Inactive IFC. Supraspinal blockade serie: IFC+Naltrindole; IFC+Naloxone; IFC+Vehicle; Inactive IFC. Intracerebral surgery was carried 3 to 5 days before joint inflammation induction. Injection of ì and ä opioid receptor antagonists intrathecally (naloxone 20 ìg/10 ìL; natrindole 5 ìg/10 ìL) and intracerebrally (naloxone 20 ìg/1 ìL; natrindole 5 ìg/1 ìL) was performed 15 minutes before treatment. Electrical stimulation was applied 24 hours after inflammation induction. Mechanical sensitivity (Von Frey) and grip strength (Grip Strengh Meter) Tests were performed before, 24 hours after inflammation induction and after IFC application. ANOVA test was used to analyze intergroup samples and two-way ANOVA test was used to evaluate repeated measures, followed by Bonferroni test for multiple comparisons. P values < 0,05 were considered significant. Animals treated with IFC showed significant greater mechanical threshold for paw withdrawal compared to pretreatment (p<0.001) and to control group (p<0.002). After pharmacological blockade of ì and ä opioid receptors either intrathecally and intracerebrally, IFC promoted significant increase in mechanical threshold (p<0.002), promoting antinociceptive effect without significant decrease in grip strength in any experimental group. IFC promoted antinociceptive effect in an animal model of inflammatory pain and its action was not mediated by spinal or supraespinal ì and ä opioid receptors.